A three-dimensional model of the boat-oars-rower system using ADAMS and LifeMOD commercial software - Serveto, S.; Barre, S.; Kobus, J.-M.; Mariot, J. -P. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
This paper presents a numerical model of the boat-oars-rower system in a three-dimensional multibody dynamics approach using the ADAMS commercial software. The system is composed of four main parts: a skiff, two oars and a rower. The boat and oar mechanical model takes into account all boat settings and kinematic constraints, thus permitting a sophisticated model personalization. The rower skeletal model is built in LifeMOD (an ADAMS plug-in) software. In the example, a skilled rower is modelled with 19 human segments and 18 human joints which are personalized to the rower using the 32 external anthropometric data of the GEBOD program. In order to focus the tests on the rower on boat model, simulations are performed with basic hydrodynamic models for a single degree of freedom for the boat at first and then three degrees of freedom are used to show the potential of the model. The model is driven with five command signals, three oar rotations, seat movement, and lower torso rotation. The computed boat velocity is in good agreement with on-water measurements and a sensitivity test consisting of small variations of rowing technique allows the authors to be confident of the ability of the model regarding future optimization studies.